Production of Cell Wall-Degrading Enzymes by the Phytopathogenic Fungus Sclerotinia sclerotiorum - Riou, Christine (1991)
The range of polysaccharide-degrading enzymes and glycosidases formed by the phytopathogenic fungus Sclerotinia sclerotiorum was monitored following growth on 16 carbohydrate substrates. Endo- and exoenzymes capable of degrading cellulosic, hemicellulosic, and pectinolytic polysaccharides were secreted. Pectinolytic activities were produced constitutively on all of the substrates tested. Cellulolytic enzymes were not induced in simple sugar (i.e., glucose or xylose) media. Polysaccharide growth substrates and cellulase inducers increased all of the enzyme activities tested. Gel filtration analysis revealed the appearance of new molecular forms of pectinase, β-xylosidase, and cellobiosidase during induction on pectin and carboxymethyl cellulose media.